Idiopathic Toe-Walking: A Review from 1967 to 2021 - Sala, Debra A. (Journal of Pediatric Neurology, 2022)
Idiopathic toe-walking (ITW) is considered a diagnosis of exclusion for which no underlying neurological, neuromuscular, neurodevelopmental, or orthopedic condition can be identified. The purpose of this review was to examine multiple aspects of ITW: natural history, evaluation, treatment, musculoskeletal manifestations, and developmental issues through the review of studies from the initial description of condition in 1967 to the present. From a PubMed search and review of reference lists of individual articles, 64 articles were selected and reviewed. The studied samples were variably described and often not well-defined. Gait analysis found gait characteristics associated with ITW that varied from normal. Children with ITW can be differentiated from children with cerebral palsy on the basis of several gait pattern features, but findings from electromyographic comparisons were variable. Treatments included orthoses, casting, botulinum toxin type A, and surgery. The evidence to support any specific treatment is limited by the small sample size and short duration of follow-up in the majority of studies. The inadequacy of the current literature suggests the need for a longitudinal multi-center study to more clearly define the population of children with ITW and to determine indications, timing, and effectiveness of the various available treatments.
Keywords: idiopathic toe-walking; casting; tendo-Achilles lengthening; botulinum toxin type A; tendo-Achilles contracture